Aplikasi ChatBot Sistem Parental Control berbasis IOT - Purnama, Giri; Ramayanti, Desi (Arcitech: Journal of Computer Science and Artificial Intelligence, 2021)
The increasing number of internet users along with the development of technology is increasing, the current webiste service users have been used by anyone and in all fields. Various sites about education, entertainment, mystical even violent scenes and pornography are things that are impossible not to find on the internet. More and more sites that are not educating at this time make parents have to be more careful and wise in supervising their children who are still under 17 years old in using internet facilities. In this study, a parental control system will be designed and built that utilizes a proxy server on a network which can later be implemented on an internet network at home. The type of research in this research is research and development to carry out system development. With this system, it is hoped that parents can be calmer at work or outside the home and their children can monitor all their activities on the internet from those that are less suitable for the child to visit.